Technical Efficiency Measurement of Cassava Production of Thailand - Parichatnon, Surakiat; Parichatnon, Kamonthip; Loatong, Poranee; Rithinyo, Manote (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2026)
Currently, cassava producers face numerous economic and natural challenges that impact production. This research aims to examine the technical efficiency of cassava cultivation under existing technologies, as well as the factors contributing to technical inefficiency in cassava cultivation in Thailand. The study uses secondary data from cassava production during the 2022/23 growing season, with a sample of 400 farmers. Data analysis is conducted through descriptive statistics and Stochastic Frontier Analysis (SFA) using a Cobb-Douglas production function model. Factors affecting technical inefficiency (TI) are analyzed using Maximum Likelihood Estimation (MLE) to estimate coefficients. The study found that the factors influencing cassava production include land area and fertilizer quantity, at a significance level of 0.01. Thailand’s average technical efficiency score stands at 0.852, indicating a high level of technical efficiency. Four factors contributed to technical inefficiency: production experience, frequency of training, age of the farmer, and disease affecting production. To maximize production efficiency, relevant agencies should support farmer training on appropriate fertilizer use, sustainable land management, plant disease prevention and control, and efficient production practices to reduce yield losses. Improving the use of these resources will enable farmers to fully enhance production efficiency, reduce environmental impact, and increase food security, aligning with Sustainable Development Goals (SDGs) Goal 2 on eliminating hunger, and Goal 12 on sustainable production and consumption.